Occupational safety and health for technologists, engineers, and managers - Goetsch, David L.; Goetsch, David L. (Upper Saddle River, New Jersey : Prentice-Hall, 2011)
Known for its comprehensive coverage, this text covers all aspects of occupational safety & health in today's global workplace.
Safety and health movement, then and now -- Accidents and their effects -- Theories of accident causation -- Roles and professional certifications for safety and health professionals -- Safety, health, and competition in the global marketplace -- The OSH act, standards, and liability -- Workers' compensation -- Accident investigation and reporting -- Product safety and liability -- Ergonomic hazards: musculoskeletal disorders (MSDS) and cumulative trauma disorders -- Stress and safety -- Safety and health training -- Violence in the workplace -- Mechanical hazards and machine safeguarding -- Falling, impact, acceleration, lifting, and vision hazards -- Hazards of temperature extremes -- Pressure hazards -- Electrical hazards -- Fire hazards and life safety -- Industrial hygiene and confined spaces -- Radiation hazards -- Noise and vibration hazards -- Computers, automation, and robots -- Blood borne pathogens in the workplace -- Preparing for emergencies and terrorism -- Ethics and safety -- Hazard analysis prevention and safety management -- Promoting safety -- Environmental safety and ISO 14000 (environmental management) -- Total safety management in a quality management setting -- Establishing a safety-friendly corporate culture.
Includes index.
Keywords: INDUSTRIAL SAFETY -- UNITED STATES